TYPES AND MAIN CHARACTERISTICS OF MONITORING TRAINING OF MODERN ECONOMIC STAFF - Delyukina, K.O. (Pedagogy of Higher and Secondary Education, 2008)
This article describes types and main characteristics of monitoring of contemporary economical staff.